Malignant cardiac phenotypic expression of Danon disease (LAMP2 cardiomyopathy). (15th October 2017) - Samad, Fatima; Jain, Renuka; Jan, M. Fuad; Sulemanjee, Nasir Z.; Menaria, Puneet; Kalvin, Lindsey; Bush, Michelle; Jahangir, Arshad; Khandheria, Bijoy K.; Tajik, A. Jamil
Abstract: Introduction: Danon disease is an X-linked lysosomal condition that causes a deficiency of lysosome-associated membrane protein 2 (LAMP2) gene. It is characterized clinically by a triad of skeletal myopathy, cardiomyopathy, and intellectual disability. Methods: We examined clinical, echocardiographic, and genetic data on 5 patients with Danon disease, highlighting their clinical course and outcomes. Results: All patients presented phenotypically with hypertrophic cardiomyopathy and later developed systolic dysfunction. The mean age at diagnosis was 19 years (11–31 years). All patients had diastolic dysfunction (mean e' of 5 cm/s [3.5–6 cm/s], mean E/e′ of 17 [15–21]). Three patients required cardiac transplantation (ages 15, 27, and 42). Of the two deaths in this group, both were in women. Conclusion: We highlight the aggressive cardiac phenotype of Danon disease in our clinical experience with rapid progression to end-stage cardiomyopathy; this progression occurred in both men and women. A timely diagnosis and an early referral for cardiac transplantation is crucial for improved outcomes.